About behaviorism - Skinner, B.F. (New York, NY Knopf, 1974)
A seminal work that delves into the depths of one of psychology's most influential and controversial philosophies. Written by a leading proponent of behaviorism, this comprehensive book offers an exploration of the principles and arguments that underpin this groundbreaking approach to understanding human behavior--Provided by publishe
D., 9/01
Keywords: Behaviorism (Psychology)